(untitled) (Cold Spring Harbor, N.Y., 2004)
This manual complements Simpson's Proteins and Proteomics manual, with a comprehensive collection of methods for protein purification from a variety of source preparations. The protocols are accompanied by extensive discussion of potential pitfalls and troubleshooting advice.
Keywords: Sự phân giải protein,Proteins,Proteomics; Thí nghiệm,Purification,Laboratory manuals.,Laboratory manuals